Pengaruh Mental Health dan Work Life Balance terhadap Turnover Intention Karyawan Gen Z di Kota Medan - Iman Putra Jaya Hulu; Sumarni Kristiani Siregar; Bayu Teta (Journal of Islamic Economics and Finance, 2025)
This study aims to analyze the influence of mental health and work-life balance on turnover intentions of Generation Z employees in Medan City. The method used in this study is quantitative involving 65 respondents as samples. The data were analyzed using multiple linear regression with SPSS version 26. The results of the validity and reliability tests indicate that the research instrument is valid and reliable. The classical assumption test has been met, including normality, multicollinearity, and heteroscedasticity. Regression analysis shows that mental health and work-life balance have a positive and significant influence, both partially and simultaneously, on turnover intentions. The Adjusted R Square value of 0.604 indicates that the two variables can explain 60.4% of the variation in turnover intentions.